ZEA-induced autophagy in TM4 cells was mediated by the release of Ca2+ activates CaMKKβ-AMPK signaling pathway in the endoplasmic reticulum. (1st May 2020) - Feng, Nannan; Wang, Bingjie; Cai, Peirong; Zheng, Wanglong; Zou, Hui; Gu, Jianhong; Yuan, Yan; Liu, Xuezhong; Liu, ZongPing; Bian, Jianchun
Graphical abstract: Highlights: ZEA promoted TM4 cells autophagy and modulated the AMPK/mTOR/P70S6K signaling pathways. AMPK signaling pathway is involved in ZEA-induced autophagy in TM4 cells. ZEA induced endoplasmic reticulum stress led to Ca 2+ release in the lumen of the endoplasmic reticulum and activated CaMKKβ. ZEA induced autophagy via Ca 2+ mediated CaMKKβ /AMPK pathway in TM4 cells. Abstract: Zearalenone (ZEA) is a prevalent non-steroidal estrogenic mycotoxin produced mainly by Fusarium contamination. Our previous study showed that ZEA induces the autophagy of Sertoli cells (SCs). However, the underlying mechanisms are still unknown. Several studies have indicated that the increasing level of cytoplasmic Ca 2+ could induce autophagy through CaMKKβ and AMPK pathways. Thus in order to investigate the potential mechanism underlying ZEA-induced autophagy, the activity of calmodulin-dependent kinase kinase β(CaMKKβ)and AMP-activated protein kinase (AMPK) signaling pathway in ZEA-infected TM4 cells was studied. In the present study, ZEA activated the CaMKKβ and AMPK signaling pathways. The AMPK inhibitor and activator significantly inhibited and stimulated the effect of ZEA on AMPK, the transformation from LC3I to LC3II, and the distribution of LC3 dots. In addition, cytosolic calcium (Ca 2+ ) was increased gradually with the concentration of ZEA. After treatment of ZEA-infected cells with 1, 2-bis (2-aminophenoxy) ethane-N, N, N', N'- tetraacetic acid- tetraac etoxymethyl ester (BAPTA-AM) and 2-aminoethyl diphenylborinate (2-APB), the intracellular concentration of Ca 2+ reduced significantly. Also, the activities of CaMKKβ and AMPK and subsequent autophagy decreased. Moreover, the antioxidant NAC significantly decreased activities of AMPK and autophagy -related protein. Therefore, it can be speculated that ROS- mediated ER-stress induced by ZEA activates AMPK via Ca 2+ -CaMKKβ leading to autophagy in TM4 cells.